AKTIVITAS ANTIOKSIDAN DAN SIFAT SENSORIS TEH CELUP CAMPURAN BUNGA KECOMBRANG, DAUN MINT DAN DAUN STEVIA. - Katrien Arumsari; siti aminah; nurrahman nurrahman (Jurnal Pangan dan Gizi, 2019)
Tea is a functional drink that widely used and developed for health purposes. The alternative ingredients for tea making are from plants such as flowers, leaves, skin, fruit, and roots. Teabags,which made from kecombrang flower, mint leaves, and stevia leaves, potentially used as functional drinks,considering the total phenol content and antioxidant activity in each ingredients. The aims of this research is to obtain tea products which contain high total phenol and antioxidant activity with optimum acceptability from kecombrang flower and mint leaves formulations. This study uses a randomized 1:1 ratio design of kecombrang flower : mint leaves, with 5 formulation:(0.4: 1.6), (0.7: 1.3), (1: 1), (1.3: 0.7) and (1.6: 0.4), to obtain the datas of Total Phenol Levels, Antioxidant Activities and Sensory characteristic of the tea. The results shows that there is significant effect on total phenol content and antioxidant activity. It results that F1 formulation has the highest amount of total phenol which is 13.907 mg as.galat / 100 mL as well as the highest antioxidant activity which is 68.84% RSA. Sensory testing produces teas with a similar color, while the taste and scent are significantly different